2007
DOI: 10.3168/jds.s0022-0302(07)71537-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine α-Lactalbumin Stimulates Mucus Metabolism in Gastric Mucosa

Abstract: Bovine alpha-lactalbumin (alpha-LA), a major milk protein, exerts strong gastroprotective activity against rat experimental gastric ulcers induced by ethanol or stress. To elucidate the mechanisms underlying this activity, the influence of alpha-LA on gastric mucus metabolism was investigated in vitro and in vivo. For the in vitro study, RGM1 cells (a rat gastric epithelial cell line) were selected for observation of the direct activity of alpha-LA on gastric mucosal cells and cultured in the presence of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…There is a distinct behaviour of cardosins upon the two dominant proteins in whey: a-La is highly susceptible to those enzymes, whereas b-lactoglobulin is not hydrolyzed to a significant extent (Barros & Malcata, 2006). This realization suggests that any peptides in WPC that may account for protection against gastric injury originated in a-La, which is in agreement with the claims by Matsumoto et al (2001), Mezzaroba et al (2006) and Ushida, Shimokawa, Toida, Matsui, and Takase (2007). On the other hand, previous studies encompassing a-La and its pancreatin hydrolyzate indicated a 32e50% decrease in ULI when two consecutive doses of 200 mg kg À1 bw were administered to rats (Matsumoto et al, 2001), whereas Mezzaroba et al (2006) described an 82% reduction under similar conditions.…”
Section: Assessment Of Antiulcerogenic Activity Of Whey Protein Hydrosupporting
confidence: 85%
“…There is a distinct behaviour of cardosins upon the two dominant proteins in whey: a-La is highly susceptible to those enzymes, whereas b-lactoglobulin is not hydrolyzed to a significant extent (Barros & Malcata, 2006). This realization suggests that any peptides in WPC that may account for protection against gastric injury originated in a-La, which is in agreement with the claims by Matsumoto et al (2001), Mezzaroba et al (2006) and Ushida, Shimokawa, Toida, Matsui, and Takase (2007). On the other hand, previous studies encompassing a-La and its pancreatin hydrolyzate indicated a 32e50% decrease in ULI when two consecutive doses of 200 mg kg À1 bw were administered to rats (Matsumoto et al, 2001), whereas Mezzaroba et al (2006) described an 82% reduction under similar conditions.…”
Section: Assessment Of Antiulcerogenic Activity Of Whey Protein Hydrosupporting
confidence: 85%
“…15) Additionally, it has been reported that α-lactalbumin fortifies the mucus gel layer by stimulating mucin production and secretion in gastric mucus-producing cells, and that this enhancing effect is independent of endogenous PGE2. 29) These results indicated that α-lactalbumin reduces the gastrointestinal side-effects.…”
Section: Discussionmentioning
confidence: 50%
“…20) aLA stimulates mucin synthesis and secretion in mucusproducing cells and induces increased thickness of the mucus gel layer in the gastric mucosa, suggesting that stimulation of mucus metabolism by aLA contributes to its gastroprotective actions.…”
Section: Discussionmentioning
confidence: 99%